Verbal interventions and exchange rate policies: The case of Swiss franc cap. (May 2019) - Mirkov, Nikola; Pozdeev, Igor; Söderlind, Paul
Highlights: Swiss National Bank (SNB) set a cap on Swiss franc at 1.20 against euro in 2011–2015. SNB's governing board members reiterated the commitment to the cap during that period. These verbal interventions lowered uncertainty regarding future euro/Swiss franc rate. SNB's verbal interventions also steered market beliefs towards franc depreciation. Abstract: We ask whether verbal interventions by the Swiss National Bank (SNB) affected market beliefs in the desired direction during the period from 2011 to 2015, when the SNB imposed a cap on the Swiss franc at 1.20 against the euro. A verbal intervention was a speech by a member of the SNB Governing Board containing the wording "utmost determination" and/or "unlimited quantities". We show that these verbal interventions lowered uncertainty regarding the future value of euro/Swiss franc exchange rate and steered market beliefs toward franc depreciation, therefore reinforcing the credibility of the Swiss franc cap.